IMPLEMENTASI MANAJEMEN KURIKULUM BERBASIS POTENSI LOKAL UNTUK MENINGKATKAN KOMPETENSI LULUSAN - R. Supyan Sauri; Fitrianingsih; Ujang Nasruloh; Dini Anggraeni Saputri Setiaji (STKIP Subang, 2025)
This study aims to describe and analyze the implementation of local potential-based curriculum management in improving graduate competencies at SDN Rancaekek 05. This study used a qualitative approach with descriptive methods. Data collection techniques included interviews, observations, and documentation studies, with the principal and teachers as subjects. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. Data validity was maintained through source and technique triangulation. The results indicate that the implementation of local potential-based curriculum management at SDN Rancaekek 05 was carried out based on the management functions according to George R. Terry: planning, organizing, implementing, and supervising. Curriculum planning was carried out by considering the characteristics of students and the school environment. Organization was carried out through the functional and collaborative division of teacher tasks. Curriculum implementation was realized through contextual learning that linked material to local potential, while supervision was carried out through ongoing supervision and evaluation. Nevertheless, curriculum implementation still faces several obstacles, including teachers' limited understanding of the local potential-based curriculum, limited supporting facilities and infrastructure, and teachers' administrative burden. To address these challenges, the school has implemented efforts to improve teacher capacity through training and mentoring, strengthening internal coordination and communication, and optimizing the use of local potential as a learning resource. Overall, the implementation of locally-based curriculum management at SDN Rancaekek 05 has contributed positively to improving graduate competencies that are contextual, relevant, and meaningful.